Pengaruh Faktor Lingkungan terhadap Perilaku Kriminalitas Anak - Salsa Desembriyanti; Risma Febrina Folasimo; Zetta Zhafira; Adinda Nur Oktafia; Tugimin Supriyadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to evaluate the impact of environmental factors on children's criminal behavior. The underlying problem of this study is that the increase in criminality among children is often influenced by the environment in which they grow up. Environmental factors such as the family's economic situation, social environment, quality of education and level of parental supervision are the main focus of this study. Based on social and child development theories, the environment plays an important role in shaping individual behavior, including the tendency to commit criminal acts. This research uses the literature study method. Data were collected without directly involving the research subjects, but rather through data collection methods. The research adopted a comprehensive literature review approach with a focus on in-depth analysis and synthesis of findings from various relevant literatures. The results show that children raised in an environment with low economic conditions, lack of attention from parents, and exposure to negative social environments tend to be more prone to engage in criminal behavior. As a solution, this study recommends improving the quality of education, educating parents on the importance of supervision, and effective social rehabilitation programs for children involved in criminal acts. It is hoped that these findings can contribute to efforts to prevent criminality among children through a more comprehensive environmental approach.